2015
DOI: 10.1080/0371750x.2015.1064327
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Mullite Bonded Porous SiC Ceramics via Sol-Gel Coated Precursor

Abstract: In the present work oxide bonded porous SiC ceramics were fabricated using surface modified sol-gel mullite coated SiC particles. The coated powder was characterized by measuring zeta potential at different pH, XRD analysis, thermal analysis and FTIR spectroscopy. To observe the role of mullite source on the properties of final ceramics two other sources of mullite (commercial mullite and synthesized mullite through sol-gel route) were also used. Porous SiC ceramics were prepared by sintering powder compact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Hence, mechanical activation as reported in this study is key to achieving a much lower mullitization temperature. Baitalik et al (2015) in their study sought to keep mullite content same in an SiC/SiC ϩ mullite composite structure in air at 1,300°C for 3 h. Notably, sintering at this temperature of 1,300°C kept the mullite content intact. No information of intense milling was recorded for this study, hence the relatively high temperature needed to keep the mullite content in the composite intact.…”
Section: World Journal Of Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, mechanical activation as reported in this study is key to achieving a much lower mullitization temperature. Baitalik et al (2015) in their study sought to keep mullite content same in an SiC/SiC ϩ mullite composite structure in air at 1,300°C for 3 h. Notably, sintering at this temperature of 1,300°C kept the mullite content intact. No information of intense milling was recorded for this study, hence the relatively high temperature needed to keep the mullite content in the composite intact.…”
Section: World Journal Of Engineeringmentioning
confidence: 99%
“…It is worthy of note that in their study, no mechanical activation was to the best of our knowledge reported to disorder the structure of the materials, hence the high temperatures reported in main conversion to mullite. Baitalik et al (2015) in their work observed the role of mullite source on the properties of final ceramics by using two sources of mullite (commercial mullite and synthesized mullite through sol-gel route). Porous SiC ceramics were prepared by sintering powder compact of mullite coated SiC/ SiC ϩ mullite particles in air at 1,300°C for 3 h keeping the mullite content same.…”
Section: Introductionmentioning
confidence: 99%